Reassessing the cost-effectiveness of high-provitamin A bananas to reduce vitamin A deficiency in Uganda - Kozicka, Marta; Elsey, Julia; Ekesa, Beatrice; Ajambo, Susan; Kikulwe, Enoch Mutebi; Gotor, Elisabetta (Frontiers Media, 2021)
There are two high-provitamin A (pVA) banana-based interventions potentially available in Uganda—biofortified genetically modified (GM) banana and fast-tracked banana landraces from outside Uganda that are naturally high in provitamin A (nHpVA). Based on the newest country statistics and using adoption scenarios obtained through focus group discussions and expert interviews, we assess obstacles and opportunities for adoption as well as cost-effectiveness of these interventions. In two alternative scenarios for the GM banana (M9 matooke), we assume 40% and 64% adoption rates, which would result in US$29,374,151 and US$63,259,415 in income saved, respectively. As an alternative, for the symmetrical scenarios, we calculate that if the nHpVA banana (Apantu plantain, native of Ghana) were to be adopted, US$46,100,148 and US$76,364,988 in income would be saved. Taking into account the full cost of R&D, we estimate that the M9 matooke could save one disability-adjusted life year (DALY) at a cost of US$67.37 at best and US$145.09 at worst. We estimate that the Apantu plantain could save one DALY at a cost of US$50.54 at best and US$83.72 at worst. Our DALY analysis estimates that all assessed HpVA banana interventions are extremely cost-effective in all scenarios, following both the World Bank's and the WHO criteria. Nevertheless, successful interventions would require extensive promotion campaigns and shifts in agricultural value chains.